Downregulation of CXCR4 Expression and Functionality After Zoledronate Exposure in Canine Osteosarcoma. (2nd June 2016) - Byrum, M.L.; Pondenis, H.C.; Fredrickson, R.L.; Wycislo, K.L.; Fan, T.M.
Abstract : Background: The establishment and progression of metastases remains the life‐limiting factor for dogs diagnosed with osteosarcoma (OS). The pattern of metastases is likely regulated through interactions between chemokine receptors and chemokines, and perturbations in these signaling cascades responsible for cytoskeletal organization and directional migration have the potential to alter metastatic cell trafficking behaviors. Hypothesis: Zoledronate will impair directional migration of OS cells through downregulation of chemokine (C‐X‐C motif) receptor 4 (CXCR4) expression and functionality. Samples: Nineteen archived tumor specimens and plasma from 20 dogs with OS. Methods: Prospectively, the expressions of CXCR4 were studied in OS cell lines and spontaneous tumor samples. The effect of zoledronate on CXCR4 expression and functionality was investigated by characterizing responses in 3 OS cell lines. In 19 OS specimens and 20 dogs with OS, changes in CXCR4 expression and circulating CXCR4 concentrations were characterized in response to zoledronate therapy respectively. Results: All canine OS cells express CXCR4, and zoledronate reduces CXCR4 expression and functionality by 27.7% ( P < .0001), through augmented proteasome degradation and reduced prenylation of heterotrimeric G‐proteins in 33% of tumor cell lines evaluated. In OS‐bearing dogs, zoledronate reduces CXCR4 expressions by 40% within the primary tumor compared to untreated controls ( P = .03) and also decreases the circulating concentrations of CXCR4 in 18 of 20 dogs with OS. Conclusions and clinical importance: Zoledronate can alter CXCR4 expression and functionality in OS cells, and consequent perturbations in CXCR4 intracellular signaling cascades might influence patterns of metastases.